2020
DOI: 10.18203/2349-2902.isj20201170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of laparoscopic and open surgery in management of 50 cases of liver hydatid cyst

Abstract: Background: Echinococcosis is caused by parasite called Echinococcus granulosus and Echinococcus multilocularis. The modern treatment of hydatid cyst of the liver varies from surgical intervention to percutaneous drainage or medical therapy.Methods: This clinical study was done on 50 patients who had liver hydatid disease admitted in Sir T Hospital, Bhavnagar from August 2013 to February 2016. Patients were divided into two groups consisting of 25 cases in each. Group A: managed by open surgery. Group B: manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The mean time durations of our study were very much comparable with study of Zaharie et al, 6 2013 where mean time duration of surgery in open method was 65 min, and in laparoscopy method, it was 72 min. Furthermore, in a study done by Gohil et al, 7 2020, they reported that those patients who had laparoscopic surgery had 76 min mean time duration.…”
Section: Discussionmentioning
confidence: 98%
“…The mean time durations of our study were very much comparable with study of Zaharie et al, 6 2013 where mean time duration of surgery in open method was 65 min, and in laparoscopy method, it was 72 min. Furthermore, in a study done by Gohil et al, 7 2020, they reported that those patients who had laparoscopic surgery had 76 min mean time duration.…”
Section: Discussionmentioning
confidence: 98%